Effects of emotional intelligence on physical activity engagement and the mediating roles of achievement motivation and interpersonal relationship in Chinese undergraduate students - Yu, Chengfeng; Xue, Aochuan; Zeng, Zhaohong; Wu, Qianjin (Frontiers in Public Health, 2024)
BackgroundEngaging in physical activity has been demonstrated to enhance cardiorespiratory fitness, muscle strength, bone health, and cardiometabolic health. However, it is concerning that more than 80% of students globally do not meet the recommended standard of at least 1 h of physical activity per day. It is imperative to enhance student involvement in physical activities.ObjectiveThis study aims to investigate the effect of emotional intelligence (EI) on undergraduate students’ physical activity engagement (PAE), to elucidate the mediating role of achievement motivation (AM) and interpersonal relationships (IR).MethodsA stratified whole-sample was used to survey 810 university students (19.84 ± 1.40 years). The scale items were designed to assess the participants’ EI, PAE, AM, and IR based on the correlation scale. SPSS and AMOS were used to analyze the mediating effect.Results and conclusionThe results demonstrated a positive effect of EI on AM and PAE (β = 0.29, p < 0.001; β = 0.28, p < 0.001). Furthermore, AM was found to have a positive effect on PAE (β = 0.07, p < 0.05). Notably, AM mediated between EI and PAE. In conclusion, our findings provide further insight into the effect of EI on undergraduate students’ PAE, and reveal the mediating role of AM.